Analysis of Scattering Angle Sampling by Multi-Angle Imaging Polarimeters for Different Orbit Geometries - Thompson, Sabrina N.; van Diedenhoven, Bastiaan; Colarco, Peter R.; Castellanos, Patricia; Lian, Eric; Martins, J. Vanderlei (Frontiers in Remote Sensing, 2022)
Per the 2017-2027 Decadal Survey for Earth Science and Applications from Space, many resources are being dedicated to identifying the most cost-effective and appropriate space-based approaches to aid in answering important questions related to the roles of aerosols, clouds, convection, and precipitation within the climate system. This includes developing advanced space-based multi-angle polarimetric imagers for observing aerosols and clouds. The information content with respect to aerosol and cloud properties of such instruments partly depends on the observed range of scattering angles. Factors influencing the sampled scattering angle range include orbit geometry, solar and viewing angle geometry and swath width. The focus of this research is to gain better insight into how each of these factors influence the scattering angle range sampled by different polarimeter platforms. Based on calculations of example precessing and sun-synchronous orbits, we conclude that the maximum observed scattering angles vary primarily with local equator crossing time (LCT) and location across the swath, while the minimum observed scattering angles vary primarily with LCT and latitude. The altitude and inclination of a precessing orbit determines the length of cycles occurring in LCT and thus in the scattering angle sampling statistics. For a nominal polarimeter with a 57˚ swath width in an orbit with 65.5˚ inclination, scattering angle ranges that are suitable for aerosol and cloud remote sensing are sampled somewhere across the swath at most covered latitudes roughly 54% of days throughout the year. Unfavorable scattering angles are observed on days where the orbit is near the terminator and LCT are early in the morning or late in the evening, when solar zenith angles are generally not suited for remote sensing. Decreasing the instrument's swath width to 7˚ primarily decreases the maximum observed scattering angle, and therefore limits the range of crossing times for which a large range of scattering angles are observed. In addition, the fraction of days throughout the year with favorable scattering angles decreases to roughly 37%. These calculations will aid in the development of next-generation observing systems using combinations of instrument platforms in different orbits, as well for other missions such as those using cubesats.